Khai thác, tập luyện hoạt động liên tưởng và huy động kiến thức trong dạy học giải bài tập môn Toán lớp 10 - Trịnh Thị Lê, Mai; Nguyễn Văn Thuận, Nguyễn Văn Thuận (Tạp chí Giáo dục, 2026)
In the context of general education reform oriented towards competency development, teaching mathematics not only aims at forming knowledge but also focuses on developing problem-solving skills through connecting and applying learned knowledge to solve mathematical problems. Through theoretical research methods, this article analyzes and synthesizes viewpoints related to associative thinking activities, knowledge activation, and the characteristics of the content of Mathematics 10, thereby proposing a process for exploiting and practicing associative thinking activities and knowledge activation in teaching problem-solving in Mathematics 10, consisting of 4 steps: (1) Identifying the content in the Mathematics 10 curriculum and the signs that evoke associations to be exploited; (2) Designing learning tasks that create opportunities for students to associate and mobilize knowledge; (3) Organizing students to solve tasks through analysis, connection, and selection of knowledge; (4) Evaluating and adjusting the results. The process is illustrated through several examples, thereby contributing to guiding teachers in designing tasks, organizing learning activities, and supporting students in using learned knowledge to solve mathematical problems in mathematics teaching.